2023
DOI: 10.1590/scielopreprints.5451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model of population densification in consolidated collective housing in the urban fabric from Juliaca city

Abstract: The analysis of the peripheries reveals the existence of important problems of residential precariousness and exclusion for a high-density collective housing project. The purpose is to model the population density in consolidated collective housing in the urban fabric of the city of Juliaca. Size and density are fundamental characteristics that define any city, but they have not always received the same attention. Although density figures prominently in any urban planning manual as a key variable governing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…There is also Calderón (2016), who conducted a study in Peru, with the aim of describing the changes exerted by the practice of yoga in the elderly, the author concluded that, the practice of yoga is a favorable practice for the elderly, increasing their lung capacity, decreasing heart rate and temperature, In addition to improvements in problems such as urinary incontinence, increased mobility, strength in the lower extremities and balance of Alzheimer's. Finally, it corresponds to the results obtained in the study conducted by Mamani and Mamani (2014), whose objective was to determine the effectiveness of yoga on the level of stress in older adults, concluding that yoga workshops significantly decreased the stress of older adults, obtaining a Tc = 11.7294 >Tt = 1.96, for which the alternative hypothesis was accepted. It is worth mentioning that, in terms of the limitations presented by the study, there is little availability of study applications that develop a proposal of yoga therapy for stress reduction in a sample similar to that of the study (older adults), another aspect that complicated the realization of the study was social isolation, because few sessions of the program were developed.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…There is also Calderón (2016), who conducted a study in Peru, with the aim of describing the changes exerted by the practice of yoga in the elderly, the author concluded that, the practice of yoga is a favorable practice for the elderly, increasing their lung capacity, decreasing heart rate and temperature, In addition to improvements in problems such as urinary incontinence, increased mobility, strength in the lower extremities and balance of Alzheimer's. Finally, it corresponds to the results obtained in the study conducted by Mamani and Mamani (2014), whose objective was to determine the effectiveness of yoga on the level of stress in older adults, concluding that yoga workshops significantly decreased the stress of older adults, obtaining a Tc = 11.7294 >Tt = 1.96, for which the alternative hypothesis was accepted. It is worth mentioning that, in terms of the limitations presented by the study, there is little availability of study applications that develop a proposal of yoga therapy for stress reduction in a sample similar to that of the study (older adults), another aspect that complicated the realization of the study was social isolation, because few sessions of the program were developed.…”
Section: Discussionsupporting
confidence: 59%
“…The definition of yoga comes from the Sanskrit language Yug which means "union" or "linity", that is, union with the whole, it is considered as a Hindu discipline, whose objective is to achieve the yoga state, that is, one in which man has recovered his true nature and feels satisfied with it. All variants of yoga have the same purpose, which is to help people find full happiness, both physically, mentally and spiritually [16]. As for the benefits of yoga, traditional doctors recommend the technique of yoga, because its practice has great benefits in promoting the health of patients, contributing significantly to their quality of life.…”
Section: Yogaterapiamentioning
confidence: 99%